Late Holocene coastal-plain evolution of the Netherlands: the role of natural preconditions in human-induced sea ingressions. Issue 2 (April 2017) - Pierik, H.J.; Cohen, K.M.; Vos, P.C.; van der Spek, A.J.F.; Stouthamer, E.
Abstract: This paper demonstrates the decisive role of natural preconditions on the formation of large late Holocene sea ingressions in peaty coastal plains along the North Sea's southern shores. Geological and archaeological evidence shows that these sea ingressions (expansion of new tidal systems) were mainly caused by land subsidence, which occurred due to intensified agricultural use of artificially drained peatlands since the Late Iron Age (250–12 BC). This made the coastal plain sensitive to storm-surge ingression through weak spots, e.g., at the location of existing creeks, in the coastline. Using The Netherlands as a case study, we show that natural preconditions (i.e., the geological setting at the time of ingression) played a key role in the pacing and extent of tidal area expansion. Ingressive tidal systems eventually reached most far inland in coastal segments with wide peaty back-barrier plains. In contrast, sea ingression formation was hampered in coastal segments with well-developed natural ingression-protecting geomorphic features (e.g., beach-barriers, supratidal levees). Feedback mechanisms, such as additional peat subsidence by loading of sediment imported into the new tidal area, caused further tidal volume increase and created accommodation space for tidal deposits. These combined effects caused irreversible sea ingression over large areas that consequently became unsuitable for habitation for many centuries. Improved understanding of such sea-ingression mechanisms and their facilitating conditions are essential for the assessment of the sensitivity of many densely populated coastal plains, which experience major human-induced subsidence, eventually leading to coastal plain drowning.